Genome-wide CRISPR screen identified NEK6 as a determinant of sensitivity to CDK4/6 inhibitor in endometrial cancer - Jian, Fangfang; Zhu, Chongying; Wang, Yiwei; Zhou, Tianyu; Yang, Chenmin; Feng, Weiwei (Frontiers in Pharmacology, 2026)
Endometrial cancer (EC) harbors highly recurrent cell cycle pathway alterations, especially hyperactivation of the CCND1/CDK4/6 axis, raising the potential for use of CDK4/6 inhibitors in these cancers. In this study, we performed a genome-wide CRISPR-Cas9-based knockout screen to identify genes that modify the response to CDK4/6 inhibitors. We found that NIMA-related kinase-6 (NEK6) levels determine the anti-tumor effects of CDK4/6 inhibitors and that NEK6 was a synthetic lethal target of CDK4/6 inhibitors in EC. We further demonstrated that combined inhibition of NEK6 and CDK4/6 resulted in marked suppression of tumor growth in vitro and in vivo. Mechanistically, NEK6 bound to Y-box binding protein-1 (YBX1) in the cytoplasm and facilitated its phosphorylation at serine 102 (p-YBX1S102), which promoted YBX1 nuclear translocation and further activated CDK2 and bcl2 transcription. As such, these data provided robust pre-clinical mechanistic evidence of synergy between NEK6 and CDK4/6 inhibitors and delineated a path for translation of these findings to preliminary clinical studies in EC patients.